Uncovering tau in wasteosomes (corpora amylacea) of Alzheimer’s disease patients - Riba, Marta; del Valle, Jaume; Romera, Clara; Alsina, Raquel; Molina-Porcel, Laura; Pelegrí, Carme; Vilaplana, Jordi (Frontiers in Aging Neuroscience, 2023)
Brain corpora amylacea, recently renamed as wasteosomes, are polyglucosan bodies that appear during aging and some neurodegenerative conditions. They collect waste substances and are part of a brain cleaning mechanism. For decades, studies on their composition have produced inconsistent results and the presence of tau protein in them has been controversial. In this work, we reanalyzed the presence of this protein in wasteosomes and we pointed out a methodological problem when immunolabeling. It is well known that to detect tau it is necessary to perform an antigen retrieval. However, in the case of wasteosomes, an excessive antigen retrieval with boiling dissolves their polyglucosan structure, releases the entrapped proteins and, thus, prevents their detection. After performing an adequate pre-treatment, with an intermediate time of boiling, we observed that some brain wasteosomes from patients with Alzheimer’s disease (AD) contained tau, while we did not detect tau protein in those from non-AD patients. These observations pointed the different composition of wasteosomes depending on the neuropathological condition and reinforce the role of wasteosomes as waste containers.